34.8k views
2 votes
Please answer this equation ❤️

Please answer this equation ❤️-example-1
User Elplatt
by
4.9k points

2 Answers

3 votes

Answer:

f(-3)=9

Solution,


f(x) = - 2 {x}^(2) - 7x + 6 \\ f( - 3) = - 2 * {( - 3)}^(2) - 7 * ( - 3) + 6 \\ \: \: \: \: \: = - 2 * 9 - ( - 21) + 6 \\ \: \: \: = - 18 + 21 + 6 \\ \: \: \: = 3 + 6 \\ \: \: \: \: \: = 9

hope this helps...

Good luck on your assignment..

User Nourdine Alouane
by
5.1k points
0 votes

Just take the function, and wherever it says 'x', substitute '-3' .

Then it'll say f(-3) = -2(-3)² - 7(-3) + 6 . Surely you can solve that.

As my old Electronic Circuits professor used to tell us, back around 1962:

"If

f(x) = -2x² - 7x + 6

then

f(cow) = -2cow² - 7cow + 6 ."

Of all the things I learned from him, this is the thing I remember most.

User Ryan Griffith
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.